2008
DOI: 10.1074/jbc.m710098200
|View full text |Cite
|
Sign up to set email alerts
|

Akt Regulates the Survival of Vascular Smooth Muscle Cells via Inhibition of FoxO3a and GSK3

Abstract: Apoptosis of vascular smooth muscle cells (VSMCs) may lead to atherosclerotic plaque instability and rupture, resulting in myocardial infarction, stroke, and sudden death. However, the molecular mechanisms mediating survival of VSMCs in atherosclerotic plaques remain unknown. Although plaque VSMCs exhibit increased susceptibility to apoptosis and reduced expression of the IGF1 receptor (IGF1R) when compared with normal VSMCs, a causative effect has not been established. Here we show that increased expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
87
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 52 publications
4
87
0
Order By: Relevance
“…39 Human plaque VSMCs show increased apoptosis in culture and in vivo, in part, because of reduced expression of the insulin-like growth factor 1 receptor, leading to reduced signaling through the serine threonine kinase Akt. 31,40 FOXO3a is inhibited by Akt, and this inhibition mediates much of the protective effect of both IGF-1 and Akt in VSMCs. 40 Thus, reduced SIRT1 activity would augment the potent proapoptotic effect of FOXO3a in VSMCs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…39 Human plaque VSMCs show increased apoptosis in culture and in vivo, in part, because of reduced expression of the insulin-like growth factor 1 receptor, leading to reduced signaling through the serine threonine kinase Akt. 31,40 FOXO3a is inhibited by Akt, and this inhibition mediates much of the protective effect of both IGF-1 and Akt in VSMCs. 40 Thus, reduced SIRT1 activity would augment the potent proapoptotic effect of FOXO3a in VSMCs.…”
mentioning
confidence: 99%
“…31,40 FOXO3a is inhibited by Akt, and this inhibition mediates much of the protective effect of both IGF-1 and Akt in VSMCs. 40 Thus, reduced SIRT1 activity would augment the potent proapoptotic effect of FOXO3a in VSMCs.…”
mentioning
confidence: 99%
“…PDGF-DD induced GSK3␤ Ser 9 phosphorylation and GSK3␤ Tyr 216 dephosphorylation in choroidal fibroblasts in vitro and in the retina in vivo. It is known that inhibition of GSK3␤ activity by Akt-dependant Ser 9 phosphorylation or through GSK3␤ Tyr 216 dephosphorylation promotes vascular cell survival (52,53). Moreover, the involvement of GSK3␤ in PDGF-DD-induced angiogenesis was confirmed by the aortic ring assay in vitro, and by the laser-induced CNV model in vivo.…”
Section: Discussionmentioning
confidence: 68%
“…7E). GSK3␤ induces vascular cell apoptosis (52). Inhibition of GSK3␤ by either Akt-dependent GSK3␤ Ser 9 phosphorylation or down-regulating its expression increases vascular cell survival (52,53).…”
Section: Pdgf-dd Regulates Gsk3␤ Phosphorylation and Expression In Vivo-mentioning
confidence: 99%
“…VSMCs are differentiated from embryonic mesenchyme, and possess the functions of contraction, and synthesis and secretion of extracellular matrix. The structure and function of VSMCs may change significantly at different developmental stages and under different physiological or pathological states (11)(12)(13)(14). Recent studies have found that various growth factors, vasoactive substances, and cytokines released from damaged endothelial vessel wall can activate VSMC surface receptors and signal transduction, which result in VSMC cell proliferation and invasion (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%